Nonstandard labour values - Ian Wright (The Open University, Economics Department, 2007)
The standard definition of labour value assumes that capitalists abstain from consumption during the period of replacement. The nonstandard definition of labour value assumes that capitalists consume. Both the transformation problem and the problem of an invariable measure of value are necessary consequences of standard labour values. In contrast, nonstandard labour values resolve both classical contradictions.
Keywords: 330; Arbeitswertlehre; Kritik; Theorie